The strange death of number controls in England: paradoxical adventures in higher education market making. Issue 9 (2nd September 2017) - McCaig, Colin; Taylor, Carol
Abstract : The paper analyses the impact of a higher education (HE) funding mechanism, the 'High Grades' policy, introduced as part of a student number control regime in England that was introduced in 2012/13 and withdrawn after only two years. This marked the end of an experiment in market making based on quality and price within a fixed student number cap. The paper analyses the impact of policy in key areas of institutional behaviour, which, taken together, illustrates why the specific HE market mechanism failed, and how longer term marketisation is affecting the different institution types in the sector in ways inimical to autonomy, equity and social justice. The paper concludes that the policy failed due to an overreliance on ideologically driven policy levers that failed to reflect the subtlety and nuance of the English HE market.